Management of Guillain-Barré Syndrome with Respiratory Distress in a Pregnant Woman: A Case Report - Wahyu Wardana, Artha; Erlangga, Muchammad Erias (Journal of Society Medicine, 2024)
Guillain-Barré Syndrome (GBS) is a rare neurological disorder characterized by the immune system's attack on the peripheral nerves. It is typically preceded by an infection, such as a respiratory or gastrointestinal infection, although the exact cause is still unknown. While GBS can occur in anyone, its occurrence during pregnancy poses unique challenges and considerations. GBS in pregnancy is relatively uncommon, but it is a critical condition that requires careful management due to the potential risks to both the mother and the developing fetus. Pregnant women with GBS may present with a variety of symptoms, including muscle weakness, tingling sensations, and loss of reflexes. These symptoms often start in the legs and can progress to the arms and upper body. Early diagnosis and early definitive treatment has promising outcome for GBS in pregnancy. We report this case to review management of GBS in pregnancy.